FORMULATION AND EVALUATION OF A MOISTURIZING CREAM USING ALMOND BUTTER (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Almond butter is one of the moisturizing agents, which has good emollient and moisturizing properties and hence can be well utilized to design a moisturizing cream, which can provide a good moisturizing property and help to maintain the healthy skin. The aim of the present study is to formulate moisturizing cream using Almond Butter and to evaluate its moisturizing property. In the present study, proper cream base was formulated by taking different trials and evaluated. The cream base showing the best results with respect to pH, thermal stability, total fatty matter and specific gravity was used for the incorporation of the active ingredient in different concentration and was evaluated for physical and chemical parameters. The subjective evaluation of the final product was carried out on volunteers of age 20 - 25 years with dry skin and moisturizing capacity was studied using corneometer. The values for pH, thermal stability, total fatty matter and specific gravity of the selected cream base were found to be within the standard limits. From the results of accelerated stability study of cream, it was found that the cream containing 3% Almond Butter was stable and effective with respect to color, odor, pH, viscosity, globule size and centrifugation. This cream was used for subjective evaluation and it was found that all the candidates experienced desired effect without any irritation. Hence it can be concluded that Almond Butter is having excellent moisturizing effect and can be used as moisturizing agent in different cosmetic products.